Estrogens and breast cancer: Mechanisms involved in obesity-related development, growth and progression. Issue 189 (May 2019) - Bhardwaj, Priya; Au, CheukMan C.; Benito-Martin, Alberto; Ladumor, Heta; Oshchepkova, Sofya; Moges, Ruth; Brown, Kristy A.
Graphical abstract: Highlights: Obesity is linked to an increased risk of developing hormone receptor positive breast cancer. Estrogens stimulate cancer development, growth and progression. The local production of estrogen in adipose tissue drives the growth of breast cancer after menopause. Abstract: Obesity is a risk factor for estrogen receptor-positive (ER+) breast cancer after menopause. The pro-proliferative effects of estrogens are well characterized and there is a growing body of evidence to also suggest an important role in tumorigenesis. Importantly, obesity not only increases the risk of breast cancer, but it also increases the risk of recurrence and cancer-associated death. Aromatase is the rate-limiting enzyme in estrogen biosynthesis and its expression in breast adipose stromal cells is hypothesized to drive the growth of breast tumors and confer resistance to endocrine therapy in obese postmenopausal women. The molecular regulation of aromatase has been characterized in response to many obesity-related molecules, including inflammatory mediators and adipokines. This review is aimed at providing an overview of our current knowledge in relation to the regulation of estrogens in adipose tissue and their role in driving breast tumor development, growth and progression.